Cyclopoid copepods in domestic water sources in three villages in Akinyele local government area of Oyo State, Nigeria (2002)
The distribution and infective rates of cyclopoid copepods ( the vectors of guineaworm, Dracunculus medinensis ) in ponds was studied in 3 infected villages in Akinyele Local Government Area of Oyo state, Nigeria during the period of September 1994 to January 1996 (the peak period of guineaworm eradication activities in the country). The density of cyclopoid copepods was highest in the dry season, reaching 149.8 copepods/litre in February 1995. The abate (Temephos) application and amount of rainfall affected the cyclops in ponds. Thermocyclops, Mesocyclops and Halicyclops species of cyclops were recovered from the ponds while none was found to be infected with D.medinensis larvae.